The development of international relations of regions-donors in the context of the implementation of the state regional policy of Russia - I. M. Ignatenko (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article considers the development of international relations of subjects of the Russian Federation as one of the main tasks of state regional policy of the country. The author notes that the international activity of regions contributes to strengthening the democratic foundations of the Russian state and has a direct influence on the formation of foreign policy and economic relations. Special attention is paid to consideration of the international activities of the donor regions of Russia.